Global surgery and burn injuries; experience from a 25 year partnership in Malawi. Issue 6 (December 2021) - Stevenson, J. Howard; Borgstein, Eric; Broadis, Emily; Chokotho, Tilinde; Watson, Stuart
Abstract: The Incidence of Burn Injuries – especially in Children – remains high in LMICs; The Lancet Commission on Global Surgery highlights the important role for increased investment to support surgically treatable conditions – including Trauma - in Developing Countries; the emphasis on delivering Funding for Healthcare improvement in Developing countries through a long-term Partnership is illustrated; encouraging early results in managing the challenge of Paediatric Burns are presented. Highlights: Global Surgery and Burn Injuries. Prevention, Training, Funding, through Partnership. Novel use of Professional Performing Arts workshops. Importance of longterm effective partnerships in attracting funding.